Les médicaments sur un marché camerounais - Sjaak Van der Geest (Anthropologie & Santé)
This essay is a reflection on anthropological research that took place many years ago (1980 and 1983) in southern Cameroon. It illustrates how medicines are sold like commodities, having effectively escaped the regulation that was intended to restrict their free exchange. This situation is common in many low-income countries and should be understood in the context of international and national transactions which lead to acute shortages of medicines in local health services. These shortages work to the advantage of those who make their living by selling medicines. Moreover, these medicine sellers render a service to patients who otherwise would not have access to medicines. Pharmaceuticalization is based on the idea that health and well-being can be purchased in the form of medicines, in other words: recovery from illness and other inconveniences requires buying medicines. But medicines also have social and political effects. They are a way of coping with situations of social and economic stress. The research used informal conversations, interviews, observations and study of documents.